Psychological well-being of Nuaulu Woman during the Nuhune Ritual: A Comparative Study of Primigravida and Multigravida - Joanne Marrijda Rugebregt; Arthur Huwae; Syahnur Rahman; Alessandra Flowrence Saija; Lidia Kastanya (Da'wa Faculty of Islamic State University Salatiga, 2025)
his study examines the differences in psychological well-being between primigravida and multigravida women of the Nuaulu tribe in Central Maluku during the Nuhune ritual—a traditional period of cultural seclusion symbolizing spiritual purification before childbirth. Employing a comparative quantitative design, the study involved 30 participants (15 primigravida and 15 multigravida), assessed using an adapted version of Ryff's Psychological Well-Being Scale. Statistical analysis using the Mann-Whitney U test revealed significantly higher well-being scores among primigravida women (U = 5.500, p < 0.05), with a large effect size (r = 0.82). These findings suggest that first-time participation in cultural-spiritual rituals may foster greater personal growth, purpose, and emotional support. The results underscore the importance of culturally grounded maternal health strategies that recognize the psychological functions of indigenous rituals. Limitations include the small sample size and cross-sectional design.